(untitled) (Scientific journal of the Fergana State University, 2026)
This article analyzes the central role of the human factor in the translation process, the translator’s cognitive activity, and the role of cognition in the perception of cultural factors. Translation is interpreted not only as the process of transferring language from one system to another, but also as a complex form of activity reflecting human thinking, cultural experience, and communicative competence. The article also examines translation examples that take cognitive and cultural factors into account as part of a practical analysis and substantiates the importance of the human factor in translation. The research findings demonstrate that translation success is directly related to the translator’s cognitive and cultural sensitivity, personal perception style, and intercultural competence.